Relaxant effect of quercetin on rabbit isolated bladder smooth muscles contractions - Hassan Sadraei; Sabihe Tabesh (Shahrekord University of Medical Sciences, 2021)
Introduction: Quercetin is a flavonoid compound found in many medicinal plants. Antispasmodic effect of quercetin has been reported in ileum and uterus smooth muscles but not in bladder. Therefore, the objective of this research was to investigate relaxant effect of quercetin in rabbit isolated bladder. Methods: Male rabbit was asphyxiated with carbon dioxide and then sacrificed. The whole bladder was dissected out and placed in oxygenated Tyrode's solution. Isolated bladder was cut into longitudinal strips and placed in an organ bath for contraction studies. Contractions were induced with KCl (20mM), acetylcholine (5μM) and electrical field stimulation (EFS). Full inhibitory concentration-response curve was constructed for quercetin following addition of above spasmogens. Quercetin was added into the organ bath with 2 fold increments in concentration until maximum response was achieved. Nifedipine was used as positive control group and equivalent volume of quercetin vehicle (water + DMSO) was used as negative control group. Results: Quercetin (4 μg/mL to 640 μg/mL) in a concentration dependent manner inhibited isolated bladder strips contracted by KCl (IC50=159±25 μg/mL), acetylcholine (IC50=43±9.1 μg/mL) and EFS (IC50=38±9.3 μg/mL). In the highest used concentration, quercetin completely removed contractile responses to KCl, acetylcholine and electrical filed stimulation (EFS). Nifedipine totally inhibited KCl response (IC50=115±36 ng/mL) but only partially inhibited acetylcholine and EFS responses. Conclusion: These results confirm the relaxant effect of quercetin on rabbit bladder and if similar effects are seen in human studies, then quercetin would be a suitable drug candidate to be investigated for bladder incontinence.